Cardio-facio-cutaneous and Noonan syndromes due to mutations in the RAS/MAPK signalling pathway: genotype–phenotype relationships and overlap with Costello syndrome. Issue 12 (17th August 2007) - Nava, Caroline; Hanna, Nadine; Michot, Caroline; Pereira, Sabrina; Pouvreau, Nathalie; Niihori, Tetsuya; Aoki, Yoko; Matsubara, Yoichi; Arveiler, Benoit; Lacombe, Didier; Pasmant, Eric; Parfait, Béatrice; et al.
Abstract : Cardio-facio-cutaneous (CFC) syndrome, Noonan syndrome (NS), and Costello syndrome (CS) are clinically related developmental disorders that have been recently linked to mutations in the RAS/MEK/ERK signalling pathway. This study was a mutation analysis of the KRAS, BRAF, MEK1 and MEK2 genes in a total of 130 patients (40 patients with a clinical diagnosis of CFC, 20 patients without HRAS mutations from the French Costello family support group, and 70 patients with NS without PTPN11 or SOS1 mutations). BRAF mutations were found in 14/40 (35%) patients with CFC and 8/20 (40%) HRAS -negative patients with CS. KRAS mutations were found in 1/40 (2.5%) patients with CFC, 2/20 (10%) HRAS -negative patients with CS and 4/70 patients with NS (5.7%). MEK1 mutations were found in 4/40 patients with CFC (10%), 4/20 (20%) HRAS -negative patients with CS and 3/70 (4.3%) patients with NS, and MEK2 mutations in 4/40 (10%) patients with CFC. Analysis of the major phenotypic features suggests significant clinical overlap between CS and CFC. The phenotype associated with MEK mutations seems less severe, and is compatible with normal mental development. Features considered distinctive for CS were also found to be associated with BRAF or MEK mutations. Because of its particular cancer risk, the term "Costello syndrome" should only be used for patients with proven HRAS mutation. These results confirm that KRAS is a minor contributor to NS and show that MEK is involved in some cases of NS, demonstrating a phenotypic continuum between the clinical entities. Although some associated features appear to be characteristic of a specific gene, no simple rule exists to distinguish NS from CFC easily.